The FT210 cell line is a mouse G2 phase mutant with a temperature-sensitive CDC2 gene product. - Th'ng, J; Wright, P; Hamaguchi, J; Lee, MG; Norbury, C; Nurse, P; Bradbury, E (1990)
The mouse cell FT210 was isolated as a G2 phase mutant with a possible defect in the histone H1 kinase. We determined that a temperature-sensitive lesion in this cell line lies in the CDC2 gene. DNA sequence analysis revealed two point mutations in highly conserved regions of the gene: an isoleucine to valine change in the PSTAIR region, and a proline to serine change at the C-terminal region of the protein p34. These mutations cause the p34 protein kinase to become inactivated and degraded in FT210 cells at the restrictive temperature, 39 degrees C. The consequence of this temperature-induced inactivation of the CDC2 gene product is cell cycle arrest at the mid to late G2 phase, and this arrest can be alleviated by the introduction of the human CDC2 homolog.